Bougainvillea at Horniman Circle Garden - Ghosh, Ayan (2023)
The Horniman Circle Garden was planned in 1869 and was completed in 1872, shortly before the Duke of Edinburgh's visit. Occupying 2.5 acres of land, the dense foliage in the garden provided a shady space to rest and was a popular meeting place for Parsis, who congregated here to enjoy the band that played music every evening after sunset.